2011
DOI: 10.1029/2010wr009137
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale error analysis, correction, and predictive uncertainty estimation in a flood forecasting system

Abstract: [1] River discharge predictions often show errors that degrade the quality of forecasts. Three different methods of error correction are compared, namely, an autoregressive model with and without exogenous input (ARX and AR, respectively), and a method based on wavelet transforms. For the wavelet method, a Vector-Autoregressive model with exogenous input (VARX) is simultaneously fitted for the different levels of wavelet decomposition; after predicting the next time steps for each scale, a reconstruction formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
74
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 90 publications
1
74
0
Order By: Relevance
“…In Montanari and Brath (2004) and Montanari and Grossi (2008) some problems of the NQT are discussed regarding its limited possibility of making the probability distribution of bivariate random variables multivariate Gaussian. However, Bogner and Pappenberger (2011) demonstrated that the application of error correction methods could minimize these problems in the case of flood forecasting purposes significantly.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Montanari and Brath (2004) and Montanari and Grossi (2008) some problems of the NQT are discussed regarding its limited possibility of making the probability distribution of bivariate random variables multivariate Gaussian. However, Bogner and Pappenberger (2011) demonstrated that the application of error correction methods could minimize these problems in the case of flood forecasting purposes significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of a sufficient amount of data is naturally very common for example in flood frequency estimation (Laio et al, 2009), downscaling of climate change scenarios for hydrological applications (Bo et al, 2007;Naveau, 2007, 2008), and hydrology in general (Zhu, 1987;Engeland et al, 2004). This paper will specifically concentrate on the impact of small sample sizes in real-time flood forecasting using ensemble driven systems in combination with the HUP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Krzysztofowicz, 2001;Pappenberger et al, 2005;Bogner and Pappenberger, 2011;Addor et al, 2011). To make the best possible decisions, forecasts with uncertainty estimates are essential.…”
Section: Introductionmentioning
confidence: 99%